2014
DOI: 10.1017/s0317167100017339
|View full text |Cite
|
Sign up to set email alerts
|

Serum Antioxidant Levels Associated with Subcortical Ischemic Vascular Disease

Abstract: vascular dementia (vad) is deemed as the second most prevalent type of dementia 1 . Subcortical ischemic vascular disease (Sivd) comprises leukoaraiosis (la) and lacunar infarction (li), which is caused by chronic hypo-perfusion or small vascular occlusion. Subcortical ischemic vascular disease is the most common cause of vad 2 and is associated with the risk of stroke 3 . With this background, the diagnosis and interference of Sivd has received extensive attention. increasing evidence ABSTRACT: Objective: We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…Subgroup analysis of two prospective cohort studies (1 publication) [19] showed that the total OR for every 1 µmol/L increment of the TBIL level for IS was 0.988 (95% CI: 0.981-0.995) after adjusting for potential risk factors, showing a signi cant difference. In the two cross-sectional studies [15,16], the summary OR for every 1 µmol/L increment of the TBIL level for IS was 0.968 (95% CI: 0.901-1.040) after adjusting for potential risk factors, showing no signi cant difference. There was mild heterogeneity in the cohort studies (I 2 = 36.0%, P = 0.211) and severe heterogeneity in the cross-sectional studies (I 2 = 91.9%, P < 0.001).…”
Section: Subgroup and Meta-regression Analysesmentioning
confidence: 94%
See 4 more Smart Citations
“…Subgroup analysis of two prospective cohort studies (1 publication) [19] showed that the total OR for every 1 µmol/L increment of the TBIL level for IS was 0.988 (95% CI: 0.981-0.995) after adjusting for potential risk factors, showing a signi cant difference. In the two cross-sectional studies [15,16], the summary OR for every 1 µmol/L increment of the TBIL level for IS was 0.968 (95% CI: 0.901-1.040) after adjusting for potential risk factors, showing no signi cant difference. There was mild heterogeneity in the cohort studies (I 2 = 36.0%, P = 0.211) and severe heterogeneity in the cross-sectional studies (I 2 = 91.9%, P < 0.001).…”
Section: Subgroup and Meta-regression Analysesmentioning
confidence: 94%
“…Five observational studies (4 publications) [10,15,16,19] explored the association between TBIL and IS for the highest versus the lowest levels of serum TBIL and for the dose-response analysis, including two prospective cohort studies (1 publications) [19], 1 case-control study [10], and two cross-sectional studies [15,16] involving 2312 ischemic stroke cases among 81,632 participants (Table 1). As Kimm 2009 separately reported results for men and women, we deemed them as two studies as mentioned previously.…”
Section: Correlation Between the Level Of Circulating Total Bilirubinmentioning
confidence: 99%
See 3 more Smart Citations